Design and Durability of Early 20Th Century Concrete Bridges in Scotland: A Review of Historic Test Data. Issue 8 (3rd August 2022) - Wilkie, Simeon; Dyer, Thomas
ABSTRACT: The development of Portland cement and concrete in the 19 th and 20 th centuries revolutionised the construction industry, and provided a means of achieving architectural and structural feats that were previously impossible. While reinforced concrete bridges provided a means of simultaneously spanning vast distances and carrying significant loads, the material was little understood and designs reflected this. As a result, many early reinforced concrete structures suffer from significant durability issues and there is a growing requirement for their maintenance and repair, but the extent of the issue is unclear. As such, this review of historic test data intends to provide insight into previous reinforced concrete bridge design in Scotland, compare their design to current engineering codes, and discuss the implications for maintaining and preserving these unique examples of architectural heritage.